The Therapeutic Potential and Molecular Mechanisms Underlying the Neuroprotective Effects of Sativex® - A Cannabis-derived Spray - Motamedy, Sina; Soltani, Bahareh; Kameshki, Halimeh; Kermani, Asmae Alipour; Amleshi, Reza Saboori; Nazeri Rezaabad, Masoud; Shabani, Mohammad (Mini-Reviews in Medicinal Chemistry, 2024)
Sativex is a cannabis-based medicine that comes in the form of an oromucosal spray. It contains equal amounts of Δ9-tetrahydrocannabinol and cannabidiol, two compounds derived from cannabis plants. Sativex has been shown to have positive effects on symptoms of amyotrophic lateral sclerosis (ALS), multiple sclerosis (MS), and sleep disorders. It also has analgesic, antiinflammatory, antitumoral, and neuroprotective properties, which make it a potential treatment option for other neurological disorders. The article reviews the results of recent preclinical and clinical studies that support the therapeutic potential of Sativex and the molecular mechanisms behind its neuroprotective benefits in various neurological disorders. The article also discusses the possible advantages and disadvantages of using Sativex as a neurotherapeutic agent, such as its safety, efficacy, availability, and legal status.
CRIS-Team Scopus Importer:2024-07-19
Keywords: amyotrophic lateral sclerosis; antitumoral; huntington's disease; multiple sclerosis; neuroprotective; Sativex